2014
DOI: 10.1002/bjs.9360
|View full text |Cite
|
Sign up to set email alerts
|

Damage control surgery for abdominal emergencies

Abstract: Background: Damage control surgery is a management sequence initiated to reduce the risk of death in severely injured patients presenting with physiological derangement. Damage control principles have emerged as an approach in non-trauma abdominal emergencies in order to reduce mortality compared with primary definitive surgery.Methods: A PubMed/MEDLINE literature review was conducted of data available over the past decade (up to August 2013) to gain information on current understanding of damage control surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
153
0
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(168 citation statements)
references
References 57 publications
1
153
0
14
Order By: Relevance
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the use of larger volumes of intraoperative peritoneal irrigation render no additional benefit for the prevention of intraabdominal sepsis, wound complications (including wound infections and evisceration episodes), or anastomotic dehiscence and enterocutaneous fistula formation events. This is also in line with the most current literature on the subject [41][42][43][44][45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…While there is experimental evidence of at least one benefit to the use of irrigation in trauma victims [39], our results strongly suggest an upper limit of 5L for the effluent. This has relevance for today's practice, since epidemiological evidence exist for the current use of Intraoperative Peritoneal Lavage for this indication in surgical practice [41][42][43][44][45][46][47][48][49][50]. Our trial has several limitations: Since damage control techniques were utilized when indicated (as per the contemporary accepted standard of care) it is very possible that the potential benefits and/or harms (or lack thereof) that the intervention has in this population remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal evidence exists to validate the benefit of damage control surgery in general surgical abdominal emergencies. Therefore, immediate surgical intervention has to be planned in well selected patients and should be used prudently 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally the management of severe cases can require such extensive and prolonged surgery that some patients may succumb intraoperatively. In managing such severe cases the damage control approach allows for temporary control of the source of insult (whether bleeding or contamination) [7]. Leaving the abdomen open allows for the patient to be transferred to an ICU for restoration of homeostasis followed by return to the operation theatre 1−2 days later for the definitive repair of organ defects.…”
Section: Damage Controlmentioning
confidence: 99%